The competition council powers in controlling the restrictive practices of the competition - Zedani, Fadila (Journal of Human Sciences, 2023)
The Competition Council plays an serious role in the economic domain, as the Algerian legislator made it a public control system which is charged with protecting free competition in the market from economic practices that restrict competition, which sometimes leads to eliminate it. Likewise, the Competition Council, as a public control authority, has wide powers that enable it to achieve a balance with the requirements of economic regulation, and this is due to its legal nature that makes it stand in the face of various violations that affect competition and eliminate them.